UV viscosity-reducing adhesive and UV viscosity-reducing adhesive tape
By using acrylate resin and polyurethane oligomers of specific compositions in UV adhesive reducing glue, the problem of migration of residual glue and reactive diluent after crosslinking is solved, and high adhesion and significantly reduced adhesion effects are achieved.
Patent Information
- Application Number
- CN202411542483.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing UV adhesive reducer is prone to residual glue after crosslinking, and the migration of the active diluent leads to a decrease in the initial viscosity and peeling force.
By using specific composition and proportions of acrylate resin and polyurethane oligomers in UV adhesive reducing glue, the use of active monomers is avoided, thereby reducing residual glue problems, and improving adhesive force before light and after light The effect of reducing adhesion.
The effect of UV detoxifying adhesive is achieved by greatly reducing the adhesion force before light and the adhesion force after light, avoiding the residual glue problem caused by the migration of active monomers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of advanced material technology, and in particular to a UV anti-viscosity adhesive and a UV anti-viscosity tape. Background Art
[0002] UV adhesive tape is a tape that has high adhesion before light exposure, but greatly reduces adhesion after light exposure. It is widely used in medical, display, semiconductor and other fields due to its excellent transparency and adhesion. After a short period of light exposure, an interpenetrating polymer network structure is formed inside the UV adhesive tape. This structure changes the fluidity, cross-linking density, free volume and surface energy of the system, thereby reducing the adhesiveness and peeling strength of the tape.
[0003] In the related art, UV viscosity-reducing adhesives are mostly acrylic resin-based adhesives, which are mixed with active monomers (also called active diluents), active diluents, photoinitiators and curing agents. However, since most active diluents in this method are small molecules, after the prepared viscosity-reducing tape is attached to the object, the small molecule active diluents will migrate to the interface of the object, causing a decrease in initial adhesion and peel strength, and the problem of residual adhesive is easy to occur after cross-linking. Summary of the invention
[0004] In view of this, the present application provides a UV viscosity-reducing adhesive and a UV viscosity-reducing tape, aiming to improve the technical problem that the existing UV viscosity-reducing adhesive is prone to residual adhesive after cross-linking.
[0005] In a first aspect, an embodiment of the present application provides a UV viscosity-reducing adhesive, which includes: 60 to 85 parts of an acrylate resin, 8 to 25 parts of a polyurethane oligomer, 0.5 to 1 parts of a curing agent, and 0.8 to 1.8 parts of a photoinitiator, and the UV viscosity-reducing adhesive does not include an active monomer.
[0006] In some embodiments of the present application, the mass fraction of the acrylic resin is 70 to 85 parts; and / or
[0007] The mass fraction of the polyurethane oligomer is 10 to 25 parts; and / or
[0008] The weight average molecular weight of the polyurethane oligomer is 900 g / mol to 3000 g / mol; and / or
[0009] The double bond content of the polyurethane oligomer is 0.3 mol / 100 g to 0.6 mol / 100 g; and / or
[0010] The UV viscosity-reducing adhesive consists of the acrylate resin, the polyurethane oligomer, the curing agent and the photoinitiator.
[0011] In some embodiments of the present application, the UV viscosity-reducing adhesive further includes a solvent, and the viscosity of the UV viscosity-reducing adhesive is 300cps to 3000cps; and / or
[0012] The curing agent comprises isocyanate; and / or
[0013] The photoinitiator includes photoinitiator 1173.
[0014] In some embodiments of the present application, the synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers. The functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid. Calculated by mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60~70): (20~30): (0.5~1.5): (0.5~1.5): (6~9).
[0015] In some embodiments of the present application, the relative molecular mass of the acrylic resin is 3500000 g / mol to 700000 g / mol; and / or
[0016] The glass transition temperature of the acrylic resin is -40°C to -15°C; and / or
[0017] The solid content of the acrylic ester resin is 35% to 50%.
[0018] In some embodiments of the present application, the soft monomer includes at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate, and ethyl acrylate; and / or
[0019] The hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile; and / or
[0020] The functional monomer comprises at least one of hydroxyethyl acrylate, acrylic acid, β-acryloxypropionic acid, glycidyl methacrylate, and acrylamide; and / or
[0021] The synthetic raw materials of the acrylic resin also include an initiator, and the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, and ammonium persulfate.
[0022] In some embodiments of the present application, the polyurethane polymer synthesis raw materials include, by mass: 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of propylene hydroxy ester, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of inhibitor.
[0023] In some embodiments of the present application, the number of double bonds in the molecular structure of the polyurethane oligomer is greater than or equal to 4; and / or
[0024] The weight average molecular weight of the polyurethane oligomer is 900 g / mol to 3000 g / mol; and / or
[0025] The double bond content of the polyurethane oligomer is 0.3 mol / 100 g to 0.6 mol / 100 g; and / or
[0026] The diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate and dicyclohexylmethane diisocyanate; and / or
[0027] The diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol; and / or
[0028] The hydroxy acrylate is selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, trimethylolpropane diacrylate, pentaerythritol triacrylate, etc.; and / or
[0029] The catalyst is at least one selected from triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, and zinc naphthenate; and / or
[0030] The polymerization inhibitor is selected from at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.
[0031] A second aspect of an embodiment of the present application provides a UV anti-viscosity tape, the UV anti-viscosity tape comprising a substrate film and the anti-viscosity adhesive located on the substrate film.
[0032] In some embodiments of the present application, the substrate film includes a PO film. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0036] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0037] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0038] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0039] UV adhesive tape is a tape that has high adhesion before light exposure, but greatly reduces adhesion after light exposure. It is widely used in medical, display, semiconductor and other fields due to its excellent transparency and adhesion. After a short period of light exposure, an interpenetrating polymer network structure is formed inside the UV adhesive tape. This structure changes the fluidity, cross-linking density, free volume and surface energy of the system, thereby reducing the adhesiveness and peeling strength of the tape.
[0040] In the related art, UV viscosity-reducing adhesives are mostly acrylic resin-based adhesives, which are then mixed with active monomers (also called active diluents), active diluents, photoinitiators and curing agents. However, since the active monomers are small molecules, after the adhesive tape is prepared and attached to the object, the small molecule active diluents will migrate to the interface of the object, causing the initial adhesion and peeling force to decrease, and it is easy to leave residual adhesive after cross-linking. It should be noted that the active monomers in this application are active monomers that can undergo cross-linking reactions under light conditions, such as acrylate monomers.
[0041] In view of this, the embodiment of the present application provides a UV viscosity-reducing adhesive, which includes, by mass: 60 to 85 parts of acrylate resin; 8 to 25 parts of polyurethane oligomer; 0.5 to 1 part of curing agent; 0.8 to 1.8 parts of photoinitiator, and the UV viscosity-reducing adhesive does not include active monomers. In the embodiment of the present application, by adding acrylate resin and polyurethane oligomer of specific composition to the UV viscosity-reducing adhesive, the UV viscosity-reducing adhesive in the embodiment of the present application has a large adhesive force before illumination, and the adhesive force is greatly reduced after illumination. In addition, the UV viscosity-reducing adhesive in the present application does not include active monomers, thereby avoiding the problem of residual adhesive caused by the migration of active monomers.
[0042] In some embodiments of the present application, the curing agent is selected from one or more of isocyanate curing agents and amine curing agents. Further, the curing agent is preferably an isocyanate curing agent.
[0043] In some embodiments of the present application, the photoinitiator is at least one of acetophenone, dibenzoyl ketone, benzil ketal, benzophenone, 1-hydroxy-cyclohexyl benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, and the like.
[0044] It should be noted that the acrylate resin in the application examples may be a commercially available acrylate resin, such as SGR-5117 (Fenghui Chemical) and TCA-9051D (Taichang Resin). The acrylate resin may also be self-developed and prepared, which is not limited here.
[0045] In some embodiments of the present application, the synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers, and the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid. Calculated by mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9).
[0046] It should be noted that the combined effect of soft monomers, hard monomers and functional monomers affects the performance of the entire acrylate polymer, and the selection and proportion of different soft monomers, hard monomers and functional monomers make the overall performance of the acrylate polymer different. In the application examples, the interaction between the polymer chains of the acrylate polymer is weaker and the mechanical properties are stable, which is conducive to improving the adhesion of the UV viscosity-reducing adhesive before light exposure.
[0047] In some embodiments of the present application, the soft monomer includes at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate, and ethyl acrylate.
[0048] In some embodiments of the present application, the hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile.
[0049] In some embodiments of the present application, the functional monomer includes at least one of hydroxyethyl acrylate, acrylic acid, β-acryloxypropionic acid, glycidyl methacrylate, and acrylamide.
[0050] It should be noted that the initiator in the present application is not particularly limited. For example, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, ammonium persulfate, and the like.
[0051] In some embodiments of the present application, the weight average molecular weight of the acrylic resin is between 350,000 g / mol and 750,000 g / mol.
[0052] The present invention also provides a method for preparing an acrylic resin, comprising the following steps:
[0053] Step (11) introducing protective gas into the reaction container.
[0054] Specifically, the reaction container is a five-necked flask, the protective gas is nitrogen, and the ventilation time is 5 min to 60 min.
[0055] Step (12) Add part of the monomer raw material into the reaction container and heat it to 65° C. to 70° C. to obtain a first reaction solution.
[0056] Specifically, a portion of the soft monomer, the hard monomer and the functional monomer are weighed and dissolved in the solvent A as a base material, added into a five-necked flask, and the stirrer is turned on and the temperature is increased.
[0057] Step (13) The first reaction solution obtained in step (12) is further heated to 70° C. to 75° C., and the remaining monomer raw materials and a portion of the initiator are added and reacted for 1 to 2 hours to obtain a second reaction solution.
[0058] Specifically, after the first reaction liquid is heated up, the remaining monomer raw materials (ie, soft monomers, hard monomers and functional monomers) and a portion of the initiator are dissolved in solvent A, and slowly added to the flask using a peristaltic pump. After the addition is completed, the reaction is carried out for about 1.5 hours to obtain the second reaction liquid.
[0059] Step (14) The second reaction liquid obtained in step (13) is further heated to 75° C. to 85° C., and the remaining initiator is added, and the reaction is continued until the monomer raw materials react completely, and then heating is stopped to obtain an acrylate resin for use.
[0060] Specifically, the remaining initiator is added dropwise to the second reaction liquid, and the reaction is continued for about 1.5 hours after the addition is completed. When the monomer raw materials are basically reacted, the heating is stopped to obtain the acrylic resin for use.
[0061] In some embodiments of the present application, the solid content of the acrylic resin prepared after step (14) is 35% to 50%. It should be noted that the reaction method is a solution polymerization reaction, and the solvent, as a carrier of the reaction, has a certain influence on the polymerization activity and the gel effect. When the solid content is set within the range of 35% to 50%, the polymerization reaction rate is moderate, the viscosity is moderate, the temperature is easy to control, the chain transfer effect is small, and it is convenient for subsequent use.
[0062] In some embodiments of the present application, the solvent A is not particularly limited. For example, the solvent A includes at least one of ethyl acetate, butyl acetate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate, dipropylene glycol ethyl ether acetate, and dipropylene glycol butyl ether acetate.
[0063] It should be noted that the polyurethane oligomers in the embodiments of the present application can be purchased directly, EBECRYL8311 or EBECRYL204 (Cytec) or CN968 or CN9013NS (Sartomer), or can be prepared by oneself, which is not limited here.
[0064] In some embodiments of the present application, the polyurethane polymer synthesis raw materials include, by mass: 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of propylene hydroxy ester, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of inhibitor.
[0065] In some embodiments of the present application, the number of double bonds in the molecular structure of the polyurethane oligomer is greater than or equal to 4.
[0066] In some embodiments of the present application, the weight average molecular weight of the polyurethane oligomer is between 900 g / mol and 3000 g / mol.
[0067] Furthermore, the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and the like.
[0068] Further, the diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol. Exemplarily, the diol is polyethylene glycol 200. Polyethylene glycol 200 has good solubility in most solvents and low cost, which is conducive to reducing the preparation cost of polyurethane oligomers.
[0069] Furthermore, the hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, trimethylolpropane diacrylate, pentaerythritol triacrylate and the like.
[0070] In some embodiments of the present application, the catalyst is selected from at least one of triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, zinc naphthenate, etc. Exemplarily, the catalyst is dibutyltin laurate. It should be noted that in the presence of dibutyltin laurate, the hydroxyl groups on the polyethylene glycol will preferentially react with the secondary aliphatic isocyanate groups on the diisocyanate, and the remaining isocyanate groups will react with the hydroxyl groups in the hydroxy acrylate, so as to ensure the successful chain extension of the reaction and obtain the polyurethane oligomer.
[0071] In some embodiments of the present application, the polymerization inhibitor is not particularly limited, such as at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.
[0072] In some embodiments of the present application, the steps of preparing the polyurethane oligomer include:
[0073] Step (21): add diisocyanate, catalyst and solvent into a reaction kettle, then add diol, and keep warm for 0.5h to 2h after adding diol, and control the reaction temperature at 40°C to 50°C.
[0074] Specifically, diisocyanate, catalyst and solvent B are first added to the reaction kettle, and then diol is slowly added dropwise for reaction, the addition time is 1.5h to 3h, and after the addition is completed, the reaction is kept warm for 0.5h to 2h, and the reaction temperature is controlled at 40° C. to 50° C. The solvent B is not particularly limited, such as at least one of ethyl acetate, butyl acetate, acetone, butanone, etc.
[0075] Step (22) Add hydroxy acrylate and polymerization inhibitor into the reaction kettle, keep the temperature for 5 to 10 hours after the addition, and raise the temperature to 50° C. to 65° C. until the reaction is completed.
[0076] Specifically, continue to drop hydroxy acrylate and polymerization inhibitor into the reactor for 0.5 to 1 hour. After the dropwise addition, keep the reaction warm for 5 to 10 hours. Raise the reaction temperature to 50°C to 65°C. After the reaction is completed, check whether the reaction is complete and cool the mixture to discharge.
[0077] In some embodiments of the present application, the step of heating to 50°C to 65°C until the reaction is completed includes: taking the reaction liquid for infrared analysis at intervals, and determining the completion of the reaction based on characteristic peaks. Specifically, the reaction liquid is taken for infrared analysis. If there is no peak near 2240cm-1, the reaction is determined to be complete, or the reaction liquid is taken for -NCO value titration. If the titration result is ≤0.5%, the reaction is determined to be complete.
[0078] In some embodiments of the present application, the solid content of the polyurethane oligomer prepared in step (22) is 40% to 60%. It should be noted that the reaction method is also a solution polymerization reaction, and the solvent, as a carrier of the reaction, has a certain influence on the polymerization activity and gel effect. When the solid content is set within the range of 40% to 60%, the polymerization reaction rate is moderate, the viscosity is moderate, and the temperature is easy to control.
[0079] The present application also provides a method for preparing a UV adhesive tape, comprising the following steps:
[0080] Step (31) provides UV viscosity-reducing adhesive solution.
[0081] Specifically, UV viscosity-reducing adhesive is added into a container, solvent A is added to adjust the viscosity, mixed evenly, and allowed to stand for defoaming to obtain adhesive solution. It should be noted that solvent A has been specifically described above and will not be repeated here.
[0082] Step (32) is to coat the UV viscosity reducing adhesive solution on the release film.
[0083] Specifically, a coating machine is used to evenly coat the adhesive on the release film. Exemplarily, the release film is PET.
[0084] Step (33) dries the release film coated with the UV viscosity reducing adhesive solution.
[0085] Specifically, the release film coated with UV viscosity-reducing adhesive is placed in an oven to dry the solvent at a temperature of 60 to 100° C. for 1 to 3 minutes, and then coated on the substrate film to obtain an adhesive tape. Exemplarily, the substrate film is one of EVA, PET, PO, and PVC, and more preferably, the substrate film is PO.
[0086] Step (34) is to put the above-mentioned tape into an oven for curing at a temperature of 40°C to 70°C for 24h to 72h. After curing is completed, a high peel strength UV anti-adhesive tape is obtained.
[0087] In some embodiments of the present application, the viscosity of the UV viscosity-reducing adhesive is 300 to 3000 cps, and more preferably, the viscosity is 500 cps to 1500 cps.
[0088] In some embodiments of the present application, the dry thickness of the adhesive layer is 10 to 30 um, and more preferably, the dry thickness of the adhesive layer is 15 um.
[0089] In some embodiments of the present application, the 180° peel strength of the UV-resistant adhesive tape at room temperature can reach more than 40N / 25mm, and the 180° peel strength after UV treatment is reduced to less than 0.3N / 25mm.
[0090] The UV adhesive tape in this application is further described below in conjunction with specific examples and experimental data.
[0091] Acrylate resin example 1 (Z11)
[0092] (1) Preparation of acrylic resin
[0093] Step 111: nitrogen was introduced into a five-necked flask for 30 min.
[0094] Step 112: 20.4 g of isooctyl acrylate, 6.9 g of methyl acrylate, 0.3 g of hydroxyethyl acrylate, 0.3 g of acrylamide, and 2.1 g of acrylic acid were dissolved in 60 g of ethyl acetate as a base material, added to a five-necked flask, stirred, and heated to 70° C. Then, 47.6 g of isooctyl acrylate, 16.1 g of methyl acrylate, 0.7 g of hydroxyethyl acrylate, 0.7 g of acrylamide, 4.9 g of acrylic acid, 0.1 g of azobisisobutyronitrile, and 30 g of ethyl acetate were slowly added dropwise, and the mixture was reacted for 3 hours after the addition was completed.
[0095] Step 113: Raise the temperature to 75° C., slowly drop 0.06 g of azobisisobutyronitrile and 30 g of ethyl acetate into the reaction bottle, and react for 1.5 hours after the dropwise addition.
[0096] Step 114: Raise the temperature to 80°C, slowly drop 0.04g of azobisisobutyronitrile and 30g of ethyl acetate into the reaction bottle, react for 1.5h after the dropwise addition, cool the material to obtain acrylate resin for standby use, and the acrylate resin has a solid content of 38%. The weight average molecular weight of the acrylate resin is 516000g / mol, and the glass transition temperature of the acrylate resin is -37°C.
[0097] Acrylate resin example 2 (Z12)
[0098] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 1.5:1.5:6. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 613000 g / mol, and the glass transition temperature of the acrylic resin is -40°C.
[0099] Acrylate resin example 3 (Z13)
[0100] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 61:30:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 599000 g / mol, and the glass transition temperature of the acrylic resin is -30°C.
[0101] Acrylate resin example 4 (Z14)
[0102] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 65:25:10 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:9. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 726000 g / mol, and the glass transition temperature of the acrylic resin is -27°C.
[0103] Acrylate resin example 5 (Z15)
[0104] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9; among which, the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8.
[0105] Acrylate resin example 6 (Z16)
[0106] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 553000 g / mol, and the glass transition temperature of the acrylic resin is -15°C.
[0107] Acrylate resin Example 7 (Z17)
[0108] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate and acrylic acid) is 68:23:9; among which, the ratio of hydroxyethyl acrylate: acrylic acid is 1:8.
[0109] Acrylate resin Example 8 (Z18)
[0110] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (acrylamide and acrylic acid) is 68:23:9; wherein the ratio of acrylamide: acrylic acid is 1:8.
[0111] Polyurethane oligomer example 1 (Z21)
[0112] Step 121: First add 30.0312g of diphenylmethane diisocyanate, 0.02679g of triethanolamine and 12.415g of acetone into a reaction kettle, and then slowly drop 12g of polyethylene glycol 200 and 30g of acetone for 1.5h. After the dropwise addition, keep the reaction warm for 1h, and control the reaction temperature at 45°C.
[0113] Step 122: Continue to drop 39.336g of pentaerythritol triacrylate, 0.0293g of toluene diphenol and 15g of acetone into the reactor for 0.5h. After the addition is complete, heat to 60°C and keep warm for 6h. The reaction liquid has no 2240cm -1 The peak is discharged near the mol / l, and the material is discharged by cooling to obtain a polyurethane oligomer for use. The weight average molecular weight of the prepared polyurethane oligomer is 980 g / mol, and the double bond content is 0.54 mol / 100 g.
[0114] Polyurethane oligomer example 2 (Z22)
[0115] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 39.8:17.9:42.2; wherein the hydroxy acrylate includes pentaerythritol triacrylate and hydroxypropyl acrylate, and the ratio of pentaerythritol triacrylate: hydroxypropyl acrylate is 19.67:8.59. The weight average relative molecular mass of the prepared polyurethane oligomer is 910 g / mol, and the double bond content is 0.38 mol / 100 g.
[0116] Polyurethane oligomer example 3 (Z23)
[0117] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 36.8:16.5:46.6; wherein the hydroxy acrylate includes pentaerythritol triacrylate and hydroxypropyl acrylate, and the ratio of pentaerythritol triacrylate: hydroxypropyl acrylate is 29.53:4.29. The weight average molecular weight of the prepared polyurethane oligomer is 950 g / mol, and the double bond content is 0.47 mol / 100 g.
[0118] Polyurethane oligomer example 4 (Z24)
[0119] The difference between the polyurethane oligomer and Example 1 is that, by mass, diphenylmethane diisocyanate is used to replace isophorone diisocyanate, and the ratio of diphenylmethane diisocyanate: polyethylene glycol 200: hydroxy acrylate is 36.9:14.7:48.3; wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 977 g / mol, and the double bond content is 0.57 mol / 100 g.
[0120] Polyurethane oligomer example 5 (Z25)
[0121] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 31.7:21.4:46.8, wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 1100 g / mol, and the double bond content is 0.51 mol / 100 g.
[0122] Polyurethane oligomer Example 6 (Z26)
[0123] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 35.4:15.9:48.5, wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 1050 g / mol, and the double bond content is 0.58 mol / 100 g.
[0124] Polyurethane oligomer Example 7 (Z27)
[0125] The difference between the polyurethane oligomer example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 40:18:42, wherein the hydroxy acrylate is hydroxybutyl acrylate. The weight average molecular weight of the prepared polyurethane oligomer is 805 g / mol, and the double bond content is 0.18 mol / 100 g.
[0126] Polyurethane oligomer Example 10 (Z28)
[0127] The difference between the polyurethane oligomer example 1 is that the mass ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 34.2:15.4:50.4, wherein the hydroxy acrylate is pentaerythritol triacrylate. The product is in a gel state, and the experiment is terminated.
[0128] The samples prepared in polyurethane oligomer Examples 1 to 10 were characterized, and the test results are shown in Table 1.
[0129] Table 1
[0130]
[0131] The acrylate resin and / or polyurethane polymer prepared in the above experimental example is prepared into a UV viscosity-reducing tape. The specific process is: add acrylate copolymer, polyurethane polymer, curing agent, photoinitiator 1173 and an appropriate amount of ethyl acetate into a cup according to a certain ratio, mix evenly, the viscosity is 1200cps, and stand to defoam. Use a coating machine to evenly apply the above glue on the PET release film. Put it in an oven at 80℃ / 2min to dry the solvent, and then transfer it to the substrate film. Put the tape in an oven and cure it at 40℃ for 72h. The raw material composition is shown in Table 2 below.
[0132] Table 2
[0133]
[0134]
[0135] Experimental test:
[0136] Peel strength test before / after illumination: The test standard is GB / T2792-2014. The specific operation is to cut a 25mmx300mm tape sample and use a universal material testing machine to perform a 180° peel strength test.
[0137] Test whether it is detached from the base film under stretching conditions: visual inspection, the specific operation is to cut a 10mmx100mm sample, use a universal material testing machine, set the initial spacing to 50mm, the stretching speed to 200mm / min, stretch the sample to break, and observe whether there is debonding.
[0138] Residual adhesive test after light exposure: visual inspection, the specific operation is to observe whether there is any residual material on the substrate after the peeling force is measured after light exposure.
[0139] The UV adhesive tapes prepared in each experimental example in Table 2 were subjected to peel strength test before illumination, peel strength test before illumination, test on whether the tapes were detached from the base film under stretching conditions, and residual adhesive test after illumination. The test results are shown in Table 3.
[0140] The UV adhesive tapes prepared in each experimental example in Table 2 were subjected to peel strength test before illumination, peel strength test before illumination, test on whether the tapes were detached from the base film under stretching conditions, and residual adhesive test after illumination. The test results are shown in Table 3.
[0141] Table 3
[0142]
[0143] In order to further study the effects of the ratios of various groups in UV anti-viscosity tapes, different substrate films and whether or not active monomers are present on the performance of UV anti-viscosity tapes, different UV anti-viscosity tapes were prepared according to the compositions in Table 4.
[0144] Table 4
[0145]
[0146]
[0147] The UV adhesive tapes prepared in each experimental example in Table 4 were subjected to peel strength test before illumination, peel strength test before illumination, test on whether the tapes were detached from the base film under stretching conditions, and residual adhesive test after illumination. The test results are shown in Table 5.
[0148] Table 5
[0149]
[0150]
[0151] It can be seen from the test results of Examples 1 to 18 that the UV anti-adhesive tapes prepared in the examples of the present application have a high adhesion before illumination, and the adhesion decreases sharply after illumination.
[0152] It can be seen from the test results of Example 1 and Example 18 that the substrate film has a great influence on the UV anti-viscosity tape prepared in the examples of the present application. The use of PO substrate film can significantly improve the bonding strength of the UV anti-viscosity tape in the examples of the present application before irradiation.
[0153] It can be seen from Example 1 and Comparative Example 2 that although a certain amount of active monomer is added to the UV viscosity-reducing adhesive of the present application, the bonding strength of the UV viscosity-reducing adhesive is reduced before irradiation, and residual adhesive exists after irradiation.
[0154] It can be seen from Example 1 and Comparative Example 1 that when the ratio of acrylate resin to polyurethane oligomer in the UV viscosity-reducing adhesive is not appropriate, for example, the amount of acrylate resin added is too low, for example, when the ratio of acrylate resin to polyurethane oligomer in Comparative Example 1 is close to 1:1, the UV viscosity-reducing adhesive has the problem of difficulty in film formation and easy debonding. When the amount of acrylate resin added in the UV viscosity-reducing adhesive is too high, for example, the amount of acrylate resin added is greater than 85 parts and the amount of polyurethane oligomer added is less than 8 parts, it is easy to cause unsatisfactory viscosity-reducing effect after illumination.
[0155] It can be seen from the test results of Examples 1 to 8 and Examples 10 to 17 and Example 9 that the combination of acrylate resin and polyurethane polymer prepared in the examples of the present application is beneficial to further improve the adhesion of the UV anti-viscosity tape before illumination. The adhesion of the UV anti-viscosity tape before illumination is above 30N / 25mm, which is a significant improvement over the adhesion of UV anti-viscosity tapes on the market before illumination (generally around 20N / 25mm), and there is no debonding or residual glue.
[0156] Furthermore, from Examples 1 to 8 and Examples 12 to 16, it can be seen that the synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers; the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid; and the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9), which is beneficial to further improve the adhesion of the UV anti-viscosity tape before illumination, so that the adhesion of the UV anti-viscosity tape before illumination is above 37N / 25mm.
[0157] Furthermore, from the test results of Example 1, Example 12 to Example 16 and Example 17, it can be seen that the raw materials for synthesizing the polyurethane polymer include: 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of hydroxy acrylate, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of inhibitor; when the hydroxy acrylate includes pentaerythritol triacrylate, it is beneficial to further reduce the bonding strength of the UV anti-viscosity tape after illumination.
[0158] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A UV viscosity-reducing adhesive, characterized in that: The UV viscosity-reducing adhesive comprises, by mass, 60 to 85 parts of an acrylate resin, 8 to 25 parts of a polyurethane oligomer, 0.5 to 1 parts of a curing agent, and 0.8 to 1.8 parts of a photoinitiator, and the UV viscosity-reducing adhesive does not include an active monomer.
2. The UV viscosity-reducing adhesive according to claim 1, characterized in that: The mass fraction of the acrylic ester resin is 70 to 85 parts; and / or The mass fraction of the polyurethane oligomer is 10 to 25 parts; and / or The weight average molecular weight of the polyurethane oligomer is 900 g / mol to 3000 g / mol; and / or The double bond content of the polyurethane oligomer is 0.3 mol / 100 g to 0.6 mol / 100 g; and / or The UV viscosity-reducing adhesive consists of the acrylate resin, the polyurethane oligomer, the curing agent and the photoinitiator.
3. The UV viscosity-reducing adhesive according to claim 1, characterized in that: The UV viscosity-reducing adhesive further comprises a solvent, and the viscosity of the UV viscosity-reducing adhesive is 300cps to 3000cps; and / or The curing agent comprises isocyanate; and / or The photoinitiator includes photoinitiator 1173.
4. The UV viscosity-reducing adhesive according to any one of claims 1 to 3, characterized in that: The synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers. The functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid. Calculated by mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9).
5. The UV viscosity-reducing adhesive according to claim 4, characterized in that: The relative molecular mass of the acrylic resin is 3500000 g / mol to 700000 g / mol; and / or The glass transition temperature of the acrylic resin is -40°C to -15°C; and / or The solid content of the acrylic ester resin is 35% to 50%.
6. The UV viscosity-reducing adhesive according to claim 4, characterized in that: The soft monomer comprises at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate and ethyl acrylate; and / or The hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile; and / or The functional monomer comprises at least one of hydroxyethyl acrylate, acrylic acid, β-acryloxypropionic acid, glycidyl methacrylate, and acrylamide; and / or The synthetic raw materials of the acrylic resin also include an initiator, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, and ammonium persulfate.
7. The UV viscosity-reducing adhesive according to any one of claims 1 to 3, characterized in that: The synthetic raw materials of the polyurethane oligomer include, by mass, 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of hydroxy acrylate, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of polymerization inhibitor.
8. The UV viscosity-reducing adhesive according to claim 7, characterized in that: The number of double bonds in the molecular structure of the polyurethane oligomer is greater than or equal to 4; and / or The diisocyanate is at least one selected from toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate; and / or The diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol; and / or The hydroxy acrylate is selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, trimethylolpropane diacrylate and pentaerythritol triacrylate; and / or The catalyst is at least one selected from triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, and zinc naphthenate; and / or The polymerization inhibitor is selected from at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.
9. A UV anti-adhesive tape, characterized in that: The UV anti-viscosity tape comprises a substrate film and the UV anti-viscosity adhesive according to any one of claims 1 to 8 located on the substrate film.
10. The UV adhesive tape according to claim 9, characterized in that: The substrate film includes a PO film.
Citation Information
Patent Citations
Antistatic UV curing high-initial-adhesion re-stripping adhesive tape and preparation method thereof
CN108659734A
Adhesive composition and UV (ultraviolet) visbreaking cutting adhesive tape
CN114517068A
Adhesive composition, UV viscosity-reducing adhesive tape and preparation method thereof
CN114517069A
UV viscosity-reducing composition, UV viscosity-reducing adhesive tape and method for preparing UV viscosity-reducing adhesive tape
CN114644900A
Viscosity-reducing adhesive composition, viscosity-reducing adhesive tape and preparation method of viscosity-reducing adhesive tape
CN115926690A